2013
DOI: 10.1111/ene.12214
|View full text |Cite
|
Sign up to set email alerts
|

p.E66Q mutation in the GLA gene is associated with a high risk of cerebral small‐vessel occlusion in elderly Japanese males

Abstract: Background and purpose: GLA is the causative gene of Fabry disease, an X-linked lysosomal storage disorder resulting from -galactosidase A (-GAL) deficiency. Stroke is an important manifestation of Fabry disease, and recent epidemiologiccal studies indicated that up to 4.9% of young male cryptogenic stroke patients have GLA mutations. To determine the importance of GLA mutations in the general stroke population, we measured the frequency of GLA mutations in Japanese male ischemic stroke patients with various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…Nakamura et al reported that the p.E66Q mutation was associated with a high risk of cerebral small-vessel occlusion in elderly Japanese men (10), and the present case presented with moderate white matter lesions, similar to the report of Nakamura et al Additionally, Takanashi et al reported that all the patients with pulvinar lesions had white matter lesions (2). Therefore, the combination of pulvinar lesions and white matter lesions in Fabry disease may have a common pathophysiology.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Nakamura et al reported that the p.E66Q mutation was associated with a high risk of cerebral small-vessel occlusion in elderly Japanese men (10), and the present case presented with moderate white matter lesions, similar to the report of Nakamura et al Additionally, Takanashi et al reported that all the patients with pulvinar lesions had white matter lesions (2). Therefore, the combination of pulvinar lesions and white matter lesions in Fabry disease may have a common pathophysiology.…”
Section: Discussionsupporting
confidence: 87%
“…Therefore, the combination of pulvinar lesions and white matter lesions in Fabry disease may have a common pathophysiology. Conversely, Nakamura et al did not observe any pulvinar lesions in their study (10). Therefore, it is difficult to determine a direct relationship between the p.E66Q mutation and the pulvinar lesion.…”
Section: Discussionmentioning
confidence: 66%
“…Lee et al further demonstrated that white blood cells derived from subjects with the E66Q enzyme display an activity 19.0-30.3% that of normal and concluded that the E66Q mutation is a functional polymorphism. However, the GLA gene E66Q mutation is a genetic risk factor for cerebral small-vessel occlusion in elderly Japanese men, according to Nakamura et al (10). We previously stated that it is questionable whether detecting the E66Q mutation in the GLA gene is adequate for predicting cerebral small-vessel occlusion (20).…”
Section: Discussionmentioning
confidence: 99%
“…We previously stated that it is questionable whether detecting the E66Q mutation in the GLA gene is adequate for predicting cerebral small-vessel occlusion (20). A study by Nakamura et al (10) used newborns as a control group. However, newborns generally do not exhibit cerebral small-vessel oc- clusion, although they may develop this complication in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation